Ethnic-territorial rights of Black Communities in the Colombian Amazon - Luis Fernando Rentería Copete (Análisis Jurídico - Político)
Thirty years after the enactment of Act 70 of 1993, which recognizes the ethnic-territorial rights of Black Communities in Colombia, including the right to collective ownership of their territories, there are still communities in different regions of the country that do not effectively benefit from this right, especially those located outside the Pacific region, such as the department of Guaviare. Until 2023, no Black Community in this region had collective ownership of its territory, despite having applied for it to the National Land Agency (ANT, Agencia Nacional de Tierras), several years earlier. The Nelson Mandela Community Council, in the municipality of Miraflores, obtained collective ownership of its territory on May 17, 2024. This event marks a historic milestone in the recognition and guarantee of the ethnic-territorial rights of Black Communities in this department of the Colombian Amazon region. This research analyzes the factors that made this ownership possible, explores the significance of this achievement for the community, identifies the good practices that facilitated the process, and points out the challenges faced by the Black Communities of Guaviare, to continue to gain ground in the collective ownership of their territories.